Pass-Through of Cost-Push Shocks - Isabel Gödl-Hanisch; Manuel Menkhoff (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper examines the pass-through of cost-push shocks to customers at a granular level. Using unique firm-level survey data, we document five facts about pass-through across firms, sectors, and over time. We highlight a new channel relevant for pass-through: beliefs about the expected duration of the shock and its interaction with price rigidities. We then employ a hypothetical vignette to study the causal effect of nominal and real rigidities as well as the nature of the shock - size, duration, and economic environment - on pass-through. We observe gradual pass-through stretching over 24 months, especially for idiosyncratic shocks, undershooting the pass-through of aggregate shocks by 40%, in line with the presence of real rigidities. The survey design further allows us to infer the implied slope of the Phillips curve, which flattens after accounting for strategic complementarities.
Keywords: E24; E31; E50; E60; 330; pass-through; cost shocks; firms; heterogeneous expectations; uncertainty; nominal rigidities; real rigidities